Multi-layered hierarchical nanostructures for transparent monolithic dye-sensitized solar cell architectures. (24th May 2017) - Passoni, Luca; Fumagalli, Francesco; Perego, Andrea; Bellani, Sebastiano; Mazzolini, Piero; Di Fonzo, Fabio
Abstract: Monolithic dye-sensitized solar cell (DSC) architectures hold great potential for building-integrated photovoltaics applications. They indeed benefit from lower weight and manufacturing costs as they avoid the use of a transparent conductive oxide (TCO)-coated glass counter electrode. In this work, a transparent monolithic DSC comprising a hierarchical 1D nanostructure stack is fabricated by physical vapor deposition techniques. The proof of concept device comprises hyperbranched TiO2 nanostructures, sensitized by the prototypical N719, as photoanode, a hierarchical nanoporous Al2 O3 spacer, and a microporous indium tin oxide (ITO) top electrode. An overall 3.12% power conversion efficiency with 60% transmittance outside the dye absorption spectral window is demonstrated. The introduction of a porous TCO layer allows an efficient trade-off between transparency and power conversion. The porous ITO exhibits submicrometer voids and supports annealing temperatures above 400 °C without compromising its optoelectronical properties. After thermal annealing at 500 °C, the resistivity, mobility, and carrier concentration of the 800 nm-thick porous ITO layer are found to be respectively 2.3 × 10 −3 Ω cm −1, 11 cm 2 V −1 s −1, and 1.62 × 10 20 cm −3, resulting in a series resistance in the complete device architecture of 45 Ω. Electrochemical impedance and intensity-modulated photocurrent/photovoltage spectroscopy give insight into the electronic charge dynamic within the hierarchical monolithic DSCs, paving the way for potential device architecture improvements.